Preparação e Caracterização de Blendas Híbridas de Poliacrilonitrila e Quitosana - Seabra, Alessandro da Cruz; da Silva Filho, Eloi Alves; Coelho, Edumar Ramos Cabral; Kock, Flávio Vinicius Crizóstomo (Orbital: The Electronic Journal of Chemistry, 2015)
In this work we report O estudo da interação de íons Fe(II) com a polianilina foi feito através da obtenção deste polímero na forma de salthe studies on polymer blend using the polymers polyacrylonitrile (PAN) and chitosan (CHI) in two compositions weight 56% PAN with 44% of CHI and 88% de PAN with 12% of CHI. We used the techniques of infrared spectroscopy (FT-IR) and scanning electron microscopy (MEV) for characterizationaplicação de pressão. The results showed that the polymer blend obtained is stable and effective interaction between PAN and CHI was observed.DOI: http://dx.doi.org/10.17807/orbital.v7i4.778